2009
DOI: 10.1074/jbc.m803997200
|View full text |Cite
|
Sign up to set email alerts
|

Integrin α6β4 Controls the Expression of Genes Associated with Cell Motility, Invasion, and Metastasis, Including S100A4/Metastasin

Abstract: The integrin ␣6␤4 is associated with carcinoma progression by contributing to apoptosis resistance, invasion, and metastasis, due in part to the activation of select transcription factors. To identify genes regulated by the ␣6␤4 integrin, we compared gene expression profiles of MDA-MB-435 cells that stably express integrin ␣6␤4 (MDA/␤4) and vector-only-transfected cells (MDA/mock) using Affymetrix GeneChip analysis. Our results show that integrin ␣6␤4 altered the expression of 538 genes (p < 0.01). Of these ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
140
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 145 publications
(152 citation statements)
references
References 52 publications
(77 reference statements)
6
140
0
4
Order By: Relevance
“…As expected, the depletion of NFAT5 decreased the S100A4 and LCN2 mRNA levels ( Figure 3a). In addition, chromatin immunoprecipitation (ChIP) assay using NFAT5 antibody indicated that NFAT5 was bound to the S100A4 and LCN2 promoters (Figure 3b, Supplementary Figure S3), as expected (Chen et al, 2009).…”
Section: Nfat5 Ddx17supporting
confidence: 76%
See 1 more Smart Citation
“…As expected, the depletion of NFAT5 decreased the S100A4 and LCN2 mRNA levels ( Figure 3a). In addition, chromatin immunoprecipitation (ChIP) assay using NFAT5 antibody indicated that NFAT5 was bound to the S100A4 and LCN2 promoters (Figure 3b, Supplementary Figure S3), as expected (Chen et al, 2009).…”
Section: Nfat5 Ddx17supporting
confidence: 76%
“…Regulation of NFAT5 by ddx5/ddx17 S Germann et al It has been reported that NFAT5 regulates the transcriptional activity of the S100A4 gene in a direct manner (Chen et al, 2009. S100A4 or metastasin, which is a member of the S100 family of calcium-binding proteins, has been shown to have an important role in breast cancer progression (Helfman et al, 2005;Garrett Regulation of NFAT5 by ddx5/ddx17 S Germann et al et al, 2006).…”
Section: Nfat5 Ddx17mentioning
confidence: 99%
“…We have found that signaling through the integrin ␣6␤4 dramatically alters the transcriptome, leading to the up-regulation of key pro-invasion and metastatic genes such as autotaxin/ ENPP2 (9), S100A4 (10), and TIAM1 (11). In this study, we find that in pancreatic carcinoma cells the integrin ␣6␤4 stimulates the expression of AREG 2 and EREG, which are ligands for EGFR.…”
mentioning
confidence: 52%
“…Furthermore, this integrin can promote pancreatic carcinoma invasiveness (11), in part through transcriptional regulation (10,11). Transcriptional profiling of integrin ␣6␤4-responsive genes (characterized in Ref.…”
Section: Resultsmentioning
confidence: 99%
“…A large body of evidence exists for the integrin‐mediated cell migration and invasion through activation of the Rho–Rac pathway 27, 28. To look for the probability of such an association in the clinical specimens, we assayed for the transcript abundance of the genes involved in this pathway.…”
Section: Resultsmentioning
confidence: 99%